(untitled) - (Film producer); Yates, David; 1963-; Rowling, J. K.; Hooper, Nicholas; Barron, David; Watson, Emma; Heyman, David; 1961-; 1989-; Grint, Rupert; 1988-; et al. (Burbank, CA, 2007)
Harry Potter, now a fifth-year student at Hogwarts School of Witchcraft and Wizardry, struggles with a threatening teacher, problematic house elf, the dread of upcoming final exams, and haunting dreams that hint toward his mysterious past.
5-8
Keywords: Potter, Harry; (Fictitious character); Juvenile fiction; Schools; Juvenile fiction; Juvenile fiction; Magic; Hogwarts School of Witchcraft and Wizardry (Imaginary organization); Juvenile fiction; Wizards; Juvenile fiction; England; Juvenile fiction; Fiction; Video recordings; Childrens films; Feature films; Fantasy films